2008
DOI: 10.1159/000187430
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Removal of Perirenal and Epididymal Adipose Tissue Decreases Serum Leptin Concentration and Increases Lipogenic Enzyme Activities in Remnant Adipose Tissue of Old Rats

Abstract: Background: The rate of lipogenesis and gene expression of lipogenic enzymes in white adipose tissue (WAT) of rats decreases with age. Previously, we showed the inverse relationship between serum leptin concentration and lipogenic enzymes activities in WAT of ageing rats. Based on those results, we postulated that leptin could play some role in the downregulation of lipogenic enzyme genes expression in WAT of old rats. Objective: To further test this hypothesis, in the present paper we examined the effect of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(48 reference statements)
2
4
0
1
Order By: Relevance
“…Consistent with no change of total fat, removal of EWAT in the present study did not alter leptin concentrations, and this is consistent with a previous report (30). There was an apparent transient increase of leptin at 4 wks post-transplantation, but it was gone by 8 wks, consistent with reports that measured leptin after 10 (24) or 12 wks (39).…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with no change of total fat, removal of EWAT in the present study did not alter leptin concentrations, and this is consistent with a previous report (30). There was an apparent transient increase of leptin at 4 wks post-transplantation, but it was gone by 8 wks, consistent with reports that measured leptin after 10 (24) or 12 wks (39).…”
Section: Discussionsupporting
confidence: 94%
“…Collectively, the results presented above indicate that WAT of females expressed progesterone receptor at higher level in inguinal versus retroperitoneal WAT, whereas in males, all main WAT depots displayed low or undetectable levels of progesterone receptor. Moreover, these results indicate that progesterone receptor in WAT, similarly as observed in other tissues [40], was downregulated by progesterone administration.…”
Section: Resultssupporting
confidence: 72%
“…8). It has been shown that progesterone can diminish the level of its own receptor in main target organs [40]. Based on these observations we decided to measure the effect of progesterone administration on progesterone receptor mRNA and protein levels in inguinal and retroperitoneal WAT of female rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin down-regulates orexigenic and up-regulates anorexigenic neuropeptide gene expression (Korner et al, 2001;Takahashi and Cone, 2005). Both our previous studies (Nogalska et al, 2009) and the experiments conducted by other authors (Gabriely et al, 2002) showed that surgical removal of adipose tissue is reflected by a decrease in the amount of circulating leptin in rats. As the assessment of changes in orexigenic and anorexigenic neuropeptide gene expression in human hypothalamus after adipose tissue removal is not possible, we examined this phenomenon in an animal model.…”
Section: Introductionmentioning
confidence: 72%